MULTIDIMENSIONAL POVERTY IN PAKISTAN: A POLICY PERSPECTIVE (Proceedings of the International Conference on Poverty and Sustainable Development, 2018)
Mostly poverty related researches have only explored monetary poverty. This empirical analysis reveals the International Multidimensional Poverty Index estimations for Pakistan. The statistical data has been gathered from the statistical Survey of “Pakistan Social and Living Standard Management” (PSLM). The Alkire and Foster (2010, 2014) methodology is used in this empirical analysis due to its instinctive and appropriate properties for policy making. The five provinces of Pakistan (including rural and urban regions) are taken such as Punjab, Sindh, Baluchistan and Khyber Pakhtunkhwan. Using PSLM statistical surveys data, we found that Pakistan’s global multidimensional poverty (MDPT) index value is 0.292 points in 2004/05, decreases significantly to 0.197 in 2014-15, while the headcount (HD) ratio dropped from 55.2% to 38.8% with (16.4% difference).Finding of this analysis shows that during all time periods multidimensional poverty (MDPT) of Pakistan remained significantly higher in rural areas as compared to urban areas. This empirical analysis provides that an integrating technique adopting for MDPT to overcome the socio-economic issues rapidly in Pakistan because it is basic requirement of millennium and sustainable development goals (MDG’s) to provide basic necessities of life (e.g., food, health, water, and education) to meet the Global standards of wellbeing.
Keywords: Poverty; health; education; welfare